(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Ramadan fasting affects lifestyle, and alterations may predispose to complications in patients with diabetes mellitus (DM). Data regarding the lifestyle during Ramadan among Bangladeshi people with DM are not adequately reported. Objectives: To see the dietary, exercise, sleep, and behavioral patterns during Ramadan fasting among Bangladeshi people with DM. Methods: This cross-sectional survey was done among diagnosed patients of DM who were fasting during the month of Ramadan 2023. Data were collected from four medical colleges, two district hospitals, and nine private chambers in a semi-structured questionnaire from the 8th to the 30th days of Ramadan. Patients filled up the questionnaire by themselves or were assisted if required. Answers were expected considering the lifestyle and behavior of the last 7 days of fasting. Results were reported among the available data. Results: Among 427 participants (age: 47.4±12.7 years, range: 14-112 years), 41.7% were males and 58.3% were females. The most common food items were different types of rice-made foods, chickpeas, fruits, fried items in the iftar and rice, animal proteins, green leafy, and other vegetables in the suhur. Around 21.4% of participants did extra physical activity other than tarawih and 29.7% in the daytime. A mean sleep duration of 1.2 hours increased during Ramadan. Around 16.5% missed at least one suhur, and 28.9% missed taking their drugs. Around 50.5% self-monitored their blood glucose at least once. Around 26.1% had to break the fast due to various reasons. Conclusions: The study findings will help clinicians to manage their patients with DM during Ramadan more effectively. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2025;4(1): 15-20